THE “TIKTOK THERAPIST”: ANALYZING THE SPREAD OF POP PSYCHOLOGY AND MENTAL HEALTH MISINFORMATION AMONG YOUTH IN SOUTHEAST ASIA - Dodi Setiawan; Pinto, Manuel; Moukadem, Rania (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The proliferation of mental health content on social media platform TikTok presents a significant challenge in Southeast Asia. Youth in the region increasingly turn to non-credentialed influencers, or “TikTok Therapists,” who disseminate pervasive pop psychology. This content often oversimplifies complex clinical conditions, creating a high-risk environment for the spread of misinformation. This study analyzes the mechanisms driving the spread of this mental health misinformation. It investigates the specific characteristics of viral pop psychology content and its perceived impact on the mental health literacy and self-diagnosis behaviors of youth in the region. A mixed-methods approach was employed, combining a large-scale digital content analysis of 500 popular mental health-related TikTok videos with a cross-sectional survey of 1,200 users (ages 16-24) across the Philippines, Indonesia, and Malaysia. The content analysis revealed that 68% of viral content originated from non-credentialed influencers, prioritizing anecdotal evidence over clinical accuracy. Survey data demonstrated a strong correlation between high TikTok consumption and increased self-diagnosis. Respondents reported trusting TikTok content due to its accessibility and its utility in bypassing significant cultural stigma associated with formal help-seeking. TikTok functions as a dual-edged, high-access environment for mental health information in Southeast Asia. While effectively destigmatizing discussion, it concurrently propagates harmful misinformation. Urgent digital literacy and critical-thinking interventions are required to mitigate these risks.